Highly Efficient Photocatalytic Degradation of Dyes by a Copper–Triazolate Metal–Organic Framework. Issue 63 (18th October 2018) - Liu, Chen‐Xia; Zhang, Wen‐Hua; Wang, Nan; Guo, Penghu; Muhler, Martin; Wang, Yuemin; Lin, Shiru; Chen, Zhongfang; Yang, Guang
Abstract: A copper(I) 3, 5‐diphenyltriazolate metal–organic framework (CuTz‐1) was synthesized and extensively characterized by using a multi‐technique approach. The combined results provided solid evidence that CuTz‐1 features an unprecedented Cu5 tz6 cluster as the secondary building unit (SBU) with channels approximately 8.3 Å in diameter. This metal–organic framework (MOF) material, which is both thermally and chemically (basic and acidic) stable, exhibited semiconductivity and high photocatalytic activity towards the degradation of dyes in the presence of H2 O2 . Its catalytic performance was superior to that of reported MOFs and comparable to some composites, which has been attributed to its high efficiency in generating . OH, the most active species for the degradation of dyes. It is suggested that the photogenerated holes are trapped by Cu I, which yields Cu II, the latter of which behaves as a catalyst for a Fenton‐like reaction to produce an excess amount of . OH in addition to that formed through the scavenging of photogenerated electrons by H2 O2 . Furthermore, it was shown that a dye mixture (methyl orange, methyl blue, methylene blue, and rhodamine B) could be totally decolorized by using CuTz‐1 as a photocatalyst in the presence of H2 O2 under the irradiation of a Xe lamp or natural sunlight. Abstract : In the frame : A thermally and chemically stable Cu I –triazolate metal–organic framework (CuTz‐1) was prepared and demonstrated to exhibit high photocatalytic activity towards the degradation of dyes in the presence of H2 O2 (see figure for dye decolorization). CuTz‐1 could be used as a catalyst for at least four cycles without significant change to the crystallinity and catalytic activity.